(untitled) (Annual Transactions of the Nordic Rheology Society, 2024)
Water-based drilling fluids are often prepared by combining polymers for viscosity and filtration control and salts for inhibition and density into a freshwater or seawater base fluid. For certain drilling operations, the desired drilling fluid density may limit the potential concentrations of salts, whereas high temperature stability may still be required. In the following the interaction effects between polymers, salts and cellulose based particles on fluid viscosity and fluid loss, and any implications for optimising recipes for low density water-based drilling fluids are presented. The viscosity impact of xanthan gum and crosslinked starch were highly dependent on the presence of salts and cellulose particles when exposed to hot-rolling at 90°C. It was found that either cellulose particles or salts were needed for the xanthan gum and crosslinked starch to retain the viscosity impact after exposure to high temperatures and mechanical wear. In contrast, the viscosity impact of polyanionic cellulose showed less viscosity interaction effects in the presence of salts and cellulose particles. A statistically significant relationship between the calculated yield stress of the fluid and the API fluid loss was identified, indicating that a higher yield strength may lead to lower fluid loss. In the tests conducted with freshwater, the addition of a selected cellulose particle blend led to more stable fluid rheology, higher fluid yield strength and lower fluid loss. In general, the introduction of mechanical wear during the hot-rolling process was found to reduce the viscosity impact of the polymers in addition to the thermal degradation, thus indicating that the rheological stability of the fluid is dependent on grinding or shearing during circulation in the wellbore.